Оптимізація складу шлаколужного в'яжучого матеріалу - Шабанова, Галина Миколаївна; Корогодська, Алла Миколаївна; Корольов, Андрій Сергійович; Нагорний, Андрій Олегович; Гапонова, Олена Олександрівна; Биканов, Сергій Миколайович (Національний технічний університет "Харківський політехнічний інститут", 2015)
У статті наведено результати розробки та оптимізації складу шлаколужного в'яжучого матеріалу, отриманого з використанням гранульованого доменного шлаку ПАТ "Дніпровський металургійний комбінат ім. Ф. Е. Дзержинського". Як активатор тверднення шлаколужного в’яжучого обрано портландцемент, для уповільнення термінів тужавіння та підвищення міцності запропоновано використовувати тонкомелений пісок. За допомогою симплекс-ґратчастого методу планування експерименту оптимізовано склад шлаколужного в'яжучого для досягнення підвищеної міцності.

The results of the development of alkali – slag binders compositions on the base of granulated blast furnace slag of PJSC "Dnipropetrovsk Metallurgical Plant named after F. E. Dzerzhinsky", Portland cement PC 1-500-N JSC of "Eurocement Ukraine" and fine grinding sand of Novovodolazhskoe field. It was determined the chemical and phase composition of the slag, the results of which established the possibility of using it to get high-quality alkali – slag binders. As activators used caustic soda and sodium water glass. Optimization of the proportion of components alkali – slag composition was performed using the simplex-lattice method of experiment planning. According to the results of experimental data calculated coefficients of expressing the dependence of the strength (Yσ) on the proportion of the components of the alkali – slag composition, construct of simplex – diagrams "composition – strength" and the projection of lines of equal level for the compositions, hardening in air and under water. It was found that for alkali – slag composition of high strength (above 25 MPa) is necessary to observe a certain proportion of slag, fine grinding sand and Portland cement.
Optimization of alkali – slag binder
Keywords: портландцемент; пісок тонкомелений; міцність; тверднення; Portland cement; fine grinding sand; strength; hardening conditions